Biochemical and Histomorphometrical Analysis Of Hepatoprotective and Hypolipidemic Potential Of Combined Herbal Extract in Diabetic Rats - Amin, MM; Mahmud, MAA (Annals of Bangladesh Agriculture, 2022)
Identical anti-diabetic effect-producing herbs (Syzygium cumini and Ficus racemosa) were administered in different doses for improved hypolipidemic and hepatoprotective effects. Experimental rats collected from icddr’b were divided into six treatment groups (control, diabetic control, standard drug, and combined herbal extracts of low, moderate, and high dose) and arranged in a Completely Randomized Design. The doses were- low (SC @ 100 mg/kg b.wt & FR @ 100 mg/kg b.wt); moderate (SC @ 300 mg/kg b.wt & FR @ 200 mg/kg b.wt) and high (SC @ 500 mg/kg b.wt & FR @ 250 mg/kg b.wt). After 30 days of experiment, blood was collected for biochemical assay and the liver was harvested for histopathologic and histomorphometric analysis. Elevated biochemical indices were significantly improved after low and moderate dose. Like biochemical parameters, histopathological abnormalities of diabetic liver were also restored within the normal range after herbal extract administration in a dose-dependent manner. Histomorphometric findings further corroborate biochemical and histological results with an increased number of healthy hepatocytes. However, high dose herbal extract did not improve these parameters satisfactorily. Collectively, these results indicated that among the three doses, moderate dose of combined extract had the best hypolipidemic and hepatoprotective effect. Ann. Bangladesh Agric. (2021) 25 (2) : 27-36